Users’ Perception towards the Adoption of Net Banking Web Face Platform in Malaysian - Ashiq, Ashiquzzaman Md; Sarwar, Abdullah; Rahman, Waliur Md (IJRDO - Journal of Business Management, 2016)
To make the banking services more convenient for their customers, banks require introducing various competitive services such as easier accessibility to e-payment. However, popularity of net banking in Malaysia is relatively low due to technophobia and negative attitudes of customers towards innovative products. Therefore, this study aimed at exploring the factors affecting the net banking adoption among Malaysian banking customers. The result shows significant influence of net banking on the perception of the Malaysian customers. However, net banking uses among Malaysian customers are being affected due to the consequences of trust factors phenomena that could be viewed as a negative sign towards the adoption of net banking.